Transdiagnostic compulsivity is associated with reduced reminder setting, only partially attributable to overconfidence - Annika Boldt; Celine Ann Fox; Claire M Gillan; Sam Gilbert (eLife)
In the current study, we explored the behavioural and cognitive correlates of the transdiagnostic trait ‘compulsive behaviour and intrusive thought’ (CIT) in humans. CIT is associated with impaired metacognition, which in turn has been associated with cognitive offloading behaviours such as external reminder setting that play a key role in fulfilling cognitive goals. In an online study (N=600), we investigated individual differences in compulsivity, metacognition, and external reminder usage. Compulsive individuals had reduced preference for external reminders. This was partially, but not fully, attributable to their relative overconfidence. In contrast to previous studies, we found no evidence for an impaired confidence-action link: compulsive individuals used their metacognition to guide offloading just as much as their non-compulsive counterparts. Given the compensatory nature of cognitive offloading, our findings imply that compulsive individuals are at increased risk of inadequate external memory support. Along with transdiagnostic variation in the general population, this finding could also have implications for clinical conditions, such as obsessive-compulsive disorder (OCD).